Efeitos de complexos de rutênio contendo 1,10-fenantrolina (FOR0211A e FOR0911A) na reatividade de aorta de rato: um estudo ex vivo e in silico - Rocha, Danilo Galvão (2025)
Nitric oxide (NO) is a gaseous free radical with high vasodilatory power, which acts by stimulating the enzyme soluble Guanylate Cyclase (sGC), and participates in several pathophysiological processes. However, current NO donors have a series of undesirable effects, such as toxicity and rapid development of tolerance. The ruthenium complexes that act on NO pathway emerge due to a search for substances that can act on the NO pathway with fewer unwanted effects. Thus, the aim of this work was to evaluate the pharmacological effect of new ruthenium complexes (FOR0211A and FOR0911A) on aortic rings isolated from rats. For this purpose, aortic rings isolated from male Wistar rats were used and mounted in an organ bath to measure isometric tension. The effect of the ruthenium complexes FOR0211A and FOR0911A (10-9 to 3x10-5 M) was evaluated on aortic rings with and without endothelium pre-contracted with Phenylephrine (PHE) 1 µM or KCl 60 mM. Furthermore, to study the mechanism of action of the complexes, the influence of NO scavengers (hydroxocobalamin and l cysteine) and inhibitors of various vascular relaxation pathways (L-NAME, ODQ, wortmannin, TEA, 4-AP, glibenclamide, BaCl2, atropine, MDL 12,330A, propranolol and indomethacin). In addition, molecular docking was carried out with the targets GCs (PDB: 7D9R), Kv (PDB: 7SIT) and Kir (PDB: 7ZDZ). After that, a study of the interaction network of proteins involved in the effect of each drug was conducted. Molecular docking experiments were also carried out using AutoDock 4.2.6 with the following targets: GCs (PDB: 7D9R and 7D9U), PI3K (PDB: 1E7U), NOS (PDB: 6CIE), bradykinin receptor (PDB: 7F2O), adenosine receptor (PDB: 5UEA), Kv (PDB: 7SIT), and Kir (PDB: 7ZDZ). The two ruthenium complexes showed a vasorelaxant effect on aortic rings pre-contracted with PHE (FOR0211A: Emax = 117.10 ± 4.44; FOR0911A: Emax = 115.80 ±1.17), however, they had less effect on pre-contracted with KCl (FOR0211A: Emax = 15.66 ± 3.52; FOR0911A: Emax = 89.47 ± 6.13). FOR0211A showed a significant reduction in effect in the presence of Hydroxocobalamin (Emax = 24.12 ± 2.90), L-Cysteine (Emax = 26.32 ± 3.25), L-NAME (Emax = 33.37 ± 8 .76), ODQ (Emax = 12.98 ± 2.03), Wortmannin (Emax = 52.41 ± 11.56), TEA (Emax = 11.32 ± 4.81), 4-AP (Emax = 15 .29 ± 4.92), glibenclamide (Emax = 76.50 ± 2.60) and BaCl2 (Emax = 40.43 ± 5.55). FOR0911A presented a significant reduction in effect in the presence of Hydroxocobalamin (Emax = 72.95 ± 6.74) and ODQ (Emax = 9.78 ± 3.77). The analysis of the protein interaction network showed that in relation to FOR0211A, there is a strong relationship of the proteins with the endogenous synthesis of NO, while with FOR0911A, there is a predominance of more direct participation of GCs. Docking showed good affinity for all targets, however, the interactions RBr+FOR0211A (-9.16 kcal/mol ± 0.94) and GCsativ+FOR0911A (-8.72 kcal/mol ± 0.02) can be highlighted due to more negative binding energy and the interactions GCsest+FOR0211A and GCsest+FOR0911A due to stronger interactions (hydrogen bonds). Thus, it can be concluded that the compounds FOR0211A and FOR0911A have a vasorelaxant effect on aortic rings, with the effect of FOR0211A probably through the eNOS/NO/sGC/cGMP pathway and potassium channels, while FOR0911A probably acts via NO donation and GCs stimulation.